2018
DOI: 10.5194/acp-18-65-2018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the molecular composition of ions and charged clusters during pure biogenic nucleation

Abstract: Abstract. It was recently shown by the CERN CLOUD experiment that biogenic highly oxygenated molecules (HOMs) form particles under atmospheric conditions in the absence of sulfuric acid, where ions enhance the nucleation rate by 1-2 orders of magnitude. The biogenic HOMs were produced from ozonolysis of α-pinene at 5 • C. Here we extend this study to compare the molecular composition of positive and negative HOM clusters measured with atmospheric pressure interface time-of-flight mass spectrometers (APi-TOFs),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 36 publications
10
55
1
Order By: Relevance
“…The same model over a larger domain found that in China, NPF contributes 26% of CCN number at 1% supersaturation despite the very high emissions of primary particles (Matsui et al, 2013). In Europe, similar studies with PMCAMx (Fountoukis et al, 2012) and GLOMAP (Reddington et al, 2011) suggest NPF is more important, increasing concentrations of particles with at least 50 nm diameter by as much as a factor of 2. Julin et al (2018) used PMCAMx with nucleation mechanisms involving both ammonia and amines to predict the consequences of future emission controls in Europe.…”
Section: 1029/2018jd029356mentioning
confidence: 77%
See 2 more Smart Citations
“…The same model over a larger domain found that in China, NPF contributes 26% of CCN number at 1% supersaturation despite the very high emissions of primary particles (Matsui et al, 2013). In Europe, similar studies with PMCAMx (Fountoukis et al, 2012) and GLOMAP (Reddington et al, 2011) suggest NPF is more important, increasing concentrations of particles with at least 50 nm diameter by as much as a factor of 2. Julin et al (2018) used PMCAMx with nucleation mechanisms involving both ammonia and amines to predict the consequences of future emission controls in Europe.…”
Section: 1029/2018jd029356mentioning
confidence: 77%
“…Recent studies have shown that oxygenated organics formed from BVOCs can grow newly nucleated particles in a wide range of troposphere temperatures (D. Stolzenburg et al, ). This is because gas phase autoxidation reactions involved in the formation of HOMs usually have strong temperature dependencies, with higher reaction rates at higher temperatures (Frege et al, ), whereas nucleation is favored at lower temperatures. Despite the low reaction rates, Bianchi et al () observed high concentrations of HOMs during NPF at a high‐elevation site with low temperatures, with an average temperature of −5 °C at noontime.…”
Section: Nucleation and Growth Mechanisms: New Results From Laboratormentioning
confidence: 99%
See 1 more Smart Citation
“…The widely observed anti-correlation between NPF and RH in the field experiments can be attributed to the indirect influence of water. For example, high RH often corresponds to greater cloud cover, which can lead to lower ground-level concentrations of photo-oxidized precursors such as H 2 SO 4 and highly oxidized molecules (HOMs) as well as an increased condensation sink that leads to scavenging of precursors and clusters (Hamed et al, 2011). On the other hand, water vapor may also directly influence NPF by regulating the formation of gas-phase precursors or by participating in cluster formation.…”
Section: Introductionmentioning
confidence: 99%
“…Field deployments of an aerosol mass spectrometer (AMS, Canagaratna et al, 2007) at several European stations have revealed a large impact of primary wood-burning emissions on OA (e.g. between 11 % and 59 % in Switzerland), while primary traffic emissions have a smaller contribution (4 %-14 %) (Lanz et al, 2010;Gilardoni et al, 2011;Daellenbach et al, 2017). The results are consistent with radiocarbon measurements (Zotter et al, 2014a), showing that during extreme winter pollution episodes non-fossil organic carbon may account for up to 97 % of organic carbon (OC) at Alpine valley sites (Magadino -83 %, San Vittore -97 %) and 74 % at an urban background site in Zurich and are also associated with levoglucosan, a pyrolysis product of cellulose.…”
Section: Introductionmentioning
confidence: 99%